De la ségrégation raciale à la « ségrégation compétitive » à Austin, Texas : les outils d’aménagement au service de politiques de peuplement ? - Marie Le Guen (Métropoles)
The fast-paced demographic and economic growth of Austin, the capital of Texas, is disrupting the previous socio-spatial distribution. The urban policies’ consequences in terms of population can be assessed through the analysis of the planning tools and the demographic categories they are based on. The economic development policies have long conditioned the population distribution, assisted by the planning policies. Nowadays, the sharpened competition between territories has made of the attraction of superior and middle class populations a high stake for urban development. The issue of the planning policies’ role is crucial to manage the resulting socio-spatial consequences, particularly the gentrification of East Austin neighborhoods. From an established racial segregation pattern, the city has now transitioned to a “competitive segregation” pattern, with a sharp affordable housing crisis that is putting to the test the various planning tools available and questioning the urban policies’ priorities.